Characteristics of flow reversal in the kinetic regime - Yogi W Budhi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2006)
In principle, reactor perturbation by flow reversal can be used for manipulation of catalyst surface coverage if a dedicated and proper operation procedure can be developed. A mathematical model and analysis of reverse flow reactor behaviour for the ammonia oxidation over platinum have been performed. Series of reverse flow experiments were carried out on a laboratory reactor scale. The influence of flow reversals on the conversion and selectivity at various switching times was observed and evaluated. Other process variables such as gas residence time, reaction temperature, and oxygen concentration in the feed were points of interest. Assessment of reactor dynamics in the kinetic regimes can be achieved most expediently by implementing a comparable switching time and gas residence time. Model and experimental results indicate that regular reverse flow operation for manipulation of catalyst surface coverage always induces a decrease of conversion. It was also found that the selectivity due to flow reversal was rather insensitive to changes in the switching frequency.Keywords: Ammonia oxidation, Kinetic regime, Reactor modeling, Residence time distribution, Reverse flow reactor operation, Transient operation AbstrakPada dasarnya pertubasi reaktor oleh aliran balik dapat digunakan untuk mengatasi penutupan permukaan katalis manakala suatu suatu prosedur operasi yang spesifik dan sesuai bisa dibangun. Analisa dan model matematika kelakuan reaktor batik untuk oksidasi amoniak pada pelat platina telah dilakukan. Serangkaian percobaan aliran balik telah dilangsungkan dalam skala laboratorium. Pengaruh aliran batik terhadap konversi dan selektivitas pada berbagaijumlah putaran aliran telah diamati dan dievaluasi. Variabel proses lainnya, seperti waktu tinggal gas, temperature reaksi, dan konsentrasi oksigen pada umpan telah menjadi perhatian pada penelitian ini. Perkiraan dinamika reaktor dalam rejim kinetika umumnya dapat diperoleh melalui penelusuran implementasi jumlah putaran aliran dan waktu tinggal gas dengan perbandingan tertentu. Hasil percobaan dan pemodelan mengindikasikan bahwa operasi aliran batik reguler untuk memanipulasi penutupan permukaan katalis selalu mengakibatkan penurunan konversi. Selain itu, ditemukan juga bahwa selectivitas terhadap pembalikan aliran kurang sensitif terhadap perubahan pada frekuensi putaran aliran.Keywords: Distribusi waktu tinggal, Operasi reaktor aliran batik, Operasi transient, Oksidasi amoniak, Pemodelan reaktor, Rejim kinetika